Comprehensive analysis of clinical and paraclinical parameters of coronary blood flow in patients with acute types of coronary artery disease and type 2 diabetes - M. A. Kokozheva; V. A. Kutsenko; B. U. Mardanov; H. R. Akhundova; M. N. Mamedov (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To study clinical and paraclinical parameters and lesions of the coronary bed in patients with acute types of coronary artery disease (CAD) and type 2 diabetes (T2D).Material and methods. The study included 102 patients of both sexes with acute CAD. Patients were analyzed in two following groups: the first (mean age, 56,6±0,96 years, men/women 34/16) consisted of 50 patients with acute coronary syndrome (ACS) and type 2 diabetes, the second (mean age, 58,7±1,01 years, men/women 37/15) — 52 patients without T2D. Along with the assessment of behavioral and biological risk factors for CVD, clinical and hemodynamic parameters and the results of coronary angiography were analyzed.Results. In patients with ACS and T2D, the duration of T2D was 5,6±3,7 years. Somatic comorbidities were registered in 74% in the first group, and in 53,8% in the second. According to echocardiography, in the group of people with ACS and T2D, the left ventricular ejection fraction was lower, and the mean pulmonary artery pressure was higher compared to the group without T2D. Stenosis of the distal coronary artery third in patients with T2D occurred in 78% of cases, and in patients without T2D — in 42%; the differences were significant (p<0,001). Diffuse CAD also prevailed in the first group and amounted to 58%, and in the second — 27%. The SYNTAX score was higher in patients with T2D compared with the group of people without T2D — 29,2 and 22%, respectively (p<0,001).Conclusion. In patients with ACS and T2D, the prevalence of pulmonary hypertension and left ventricular systolic dysfunction was revealed. The features of the coronary flow in patients with T2D with ACS were predominantly the distal type of lesion, as well as an increased risk of angioplasty complications, assessed using the SYNTAX score.